MANAJEMEN MADRASAH DALAM MENINGKATKAN PROFRSIONALITAS GURU DI MTSN 8 MUARO JAMBI - M. Junaidi Habe; Maisyah Maisyah; Fadlilah; Rafik Darmansyah; Erni Sumawati; Indra Ryuani; Alisayh Pitri; Yanfaunnas Yanfaunnas (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2022)
This research is motivated by the existence of various gaps in the field so it is urgent to find a solution. The main gap or problem encountered in the field is the lack of planning. The weak planning of the madrasah principal is indicated by the discovery of several problems such as: teachers who teach not in accordance with their scientific competence, lack of learning media and lack of attention from madrasah principals to teachers who excel. The purpose of this study is to describe the planning carried out by the head of the madrasa in improving the professionalism of teachers at the school, as well as what obstacles and efforts have been made. The method used is qualitative, by collecting data in the form of observations, interviews, and documentation. The findings of this study are: (1) The planning carried out to increase the professionalism of teachers at MTSN 8 Muaro Jambi has not been carried out optimally. In this case the learning planning carried out by the principal to improve the quality of teacher professionalism is in the form of orders without any coordination and supervision efforts, in this case it is also seen that teachers teach not in their specialization and teach as they are without mastering the material in depth. (2) The factor that becomes an obstacle in planning to increase teacher professionalism at MTSN 8 Muaro Jambi is the recruitment of teachers who are not in accordance with the needs of the school. And the lack of a relationship between the principal and parties outside the government then the supporting infrastructure factor in the school is very minimal. (3) Planning efforts to increase teacher professionalism at MTSN 8 Muaro Jambi, namely the school principal always tries to provide motivation and orders so that teachers can make lesson plans before teaching, although this has not been done effectively.